1973
DOI: 10.1113/jphysiol.1973.sp010227
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous salivation in the rabbit submandibular gland

Abstract: summABY 1. Salivation has been studied in the submandibular gland of the rabbit. A very slow spontaneous salivation took place when all possibility of nerve influence had been excluded. Salivation was not due to ultrafiltration.2. The 'spontaneous' saliva had a mean K concentration of 148 mM and Na concentration of 46 mm. With increasing salivation rate produced by parasympathetic nerve stimulation, K concentration fell to a plateau level of about 30 mm whilst Na concentration fell rapidly to reach the low val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…In the 'control' glands the mean value was 0-29 + 0 15 ul min-' gwith a range of 0 18-0-5 #1 min-' g-', which is similar to the results of Smaje (1973) and Gj6rstrup (1977) for normal spontaneous flow.…”
Section: Sympathetic Denervationssupporting
confidence: 86%
See 1 more Smart Citation
“…In the 'control' glands the mean value was 0-29 + 0 15 ul min-' gwith a range of 0 18-0-5 #1 min-' g-', which is similar to the results of Smaje (1973) and Gj6rstrup (1977) for normal spontaneous flow.…”
Section: Sympathetic Denervationssupporting
confidence: 86%
“…The 'spontaneous' flow from the glands that were contralateral to the parasympathetically decentralized glands tended to be greater than that recorded in normal animals (Smaje, 1973;Gj6rstrup, 1977). The explanation for this is not clear but it does indicate that some changes have occurred in the control glands, contralateral to the parasympathectomized ones, and therefore they should not be regarded as truly normal glands.…”
Section: Discussionmentioning
confidence: 77%
“…Calibration was made by injection of a set amount of saline solution into the bottle, and sensitivity of the recording system was determined to measure salivary flow ranging from 0 5 to 100 jf1l. Within this range, however, it was difficult to record a spontaneous secretion, because Smaje (1973) reported that the flow rate of spontaneous secretion was rather slow in submandibular glands ofrabbits, i.e. 0-25 #1l./g.min on average (n = 11).…”
Section: Methodsmentioning
confidence: 99%
“…The sweat of children suffering from cystic fibrosis has a raised [Na] which has been shown to be a result of a defect in ductal Na reabsorption (Schulz, 1969). Chronic ligation of the main duct of the rabbit submandibular gland leads to an increase in [Na] in spontaneously secreted saliva (Smaje, 1973) but it is not clear whether this 24P PHYSIOLOGICAL SOCIETY, SEPTEMBER 1978 is also due to deficiency in the ductal Na reabsorptive mechanism. The present experiments were designed to investigate this possibility.…”
Section: P Physiological Society September 1978mentioning
confidence: 97%